The little flower shop ebook - Foster, Lori (2023)
"The author masterfully blends heat and sweet in a fast-paced plot helmed by a charming hero and heroine. The result is exactly the heartwarming happily ever after that Foster's fans expect." —Publishers Weekly on The Little Flower Shop How did her love life become a community affair? Since her divorce, Emily Lucretia—affectionately known as the flower lady to the people of Cemetery, Indiana—has been focused on her flower shop and taking care of her aging aunt and uncle. Her love life is hardly the centerpiece of her busy days. Saul Culver, the town's favorite bachelor and owner of the local barbecue joint, has been interested in Emily for a while. But as much as Emily knows about flowers, she can be a little oblivious to her own appeal. Saul is determined to show her just how special she is. Saul isn't the only one trying to get Emily out of her shell. Well-meaning locals have started tagging photos of Emily with #theflowerlady on social media—and now the entire town is involved in finding her Mr. Right. Saul won't give up easily. He's finally caught her attention, and he's determined to convince Emily—and the town—that this is the real deal and not just some passing trend. Don't miss The Love Shack , an all-new heart-stirring romance from New York Times bestselling author Lori Foster about Berkley Carr, who, while running her animal haven, must confront her past and the undeniable chemistry she shares with her neighbor in a small town determined to play matchmaker. More charming contemporaries from Lori Foster: The Little Flower Shop The Honeymoon Cottage The Somerset Girls The Summer of No Attachments Sisters of Summer's End